Transforming healthcare delivery: a descriptive study of a novel provider-to-provider virtual care platform - Tennankore, Karthik; Jones, Jennifer; Miller, Ashley; Adib, Ashfaq; Mathew, Shan; Rasic, Daniel; Cookey, Jacob (Frontiers in Public Health, 2023)
Introduction Addressing challenges in access to specialty care, particularly long wait times and geographic disparities, is a pressing issue in the Canadian healthcare system. This study aimed to evaluate the impact and feasibility of provider-to-provider phone consultations between primary care providers (PCPs) and specialists using a novel virtual care platform in Nova Scotia (Virtual Hallway). Methods We conducted a cross-sectional survey over 5 months, involving 211 PCPs and 34 specialists across Nova Scotia. The survey assessed the need for formal in-person referrals as well as clinician satisfaction. Statistical methods included descriptive statistics and the one-sample t-test. Results We found that 84% of provider-to-provider phone consultations negated the need for an in-person specialist referral. It was also reported that 90% of patients that did require in-person consultation had enhanced care while they awaited an in-person appointment with a specialist. Very high levels of satisfaction were reported among both PCPs and specialists, and there was a noticeable increase in billing volumes related to these consultations as measured by provincial billing codes. Conclusion The findings indicate that provider-to-provider phone consultations are feasible, well-accepted and also effective in reducing the need for in-person specialist visits. This approach offers a promising avenue for alleviating waitlist burdens, enhancing the quality of care, and improving the overall efficiency of healthcare delivery.